Factors Affecting Student Accounting Practicum Learning Outcomes During the Covid-19 Pandemic - Joni Susilowibowo; Susanti Susanti; Han Tantri Hardini; Irin Widayati; Moh. Danang Bahtiar (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2021)
The COVID-19 pandemic has changed the quality of education, one of which can be seen from the good and bad learning outcomes of students. Therefore, this study aims to examine the factors that influence the learning outcomes of Accounting Practicum courses including student characteristics, initial ability and use of learning videos. The sample in this study amounted to 57 students. Data collection techniques in the form of questionnaires and learning outcomes while data analysis techniques using multiple regression. The results of the study indicate that: (1) There is no influence between student characteristics on the learning outcomes of Accounting Practicum, (2). there is an influence between initial ability on learning outcomes of Accounting Practicum, (3). There is an effect of the use of learning videos on the learning outcomes of Accounting Practicum, and (4). There is a simultaneous influence between student characteristics, initial ability, and the use of learning videos on the learning outcomes of the Accounting Practicum course. The implication of this research is that students' initial abilities are shown by good academic knowledge coupled with lecturers' efforts in using learning videos to improve student learning outcomes so that lecturers hope that they can apply them in learning.